2017
DOI: 10.3892/ol.2017.7620
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of membrane-type Tim-3 on hepatocellular carcinoma Hepa1-6 cells of ICR mice

Abstract: Abstract. In the present study, the inhibitory effect of transmembrane Tim-3 on hepatocellular carcinoma Hepa1-6 cells and the potential application of Tim-3 on immune system of Institute of Cancer Research (ICR) mice loaded with Hepa1-6 hepatocellular carcinoma was investigated. The animal model was established via inoculation of Hepa1-6 hepatocarcinoma cells at the hind thigh of ICR mice. Recombinant vector plasmids were transfected at the same site for gene therapy by injection to observe the inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These findings provided the mechanism by which TIPE-2 promotes apoptosis of hepatocellular carcinoma. In the study by Liu J et al [72] it was revealed that the growth of tumor was significantly suppressed after the transfection of T-cell immunoglobulin and mucin-domain containing-3. In the presence of T-cell immunoglobulin and mucin-domain containing-3 (Tim-3), the proliferation of splenocytes and cytolysis in the early phase of tumor development was significantly enhanced.…”
Section: Studiesmentioning
confidence: 99%
“…These findings provided the mechanism by which TIPE-2 promotes apoptosis of hepatocellular carcinoma. In the study by Liu J et al [72] it was revealed that the growth of tumor was significantly suppressed after the transfection of T-cell immunoglobulin and mucin-domain containing-3. In the presence of T-cell immunoglobulin and mucin-domain containing-3 (Tim-3), the proliferation of splenocytes and cytolysis in the early phase of tumor development was significantly enhanced.…”
Section: Studiesmentioning
confidence: 99%